Study on strain-tuned structural, mechanical, electronic, and optical properties of cubic SiSnO3 perovskite from DFT and GW0 scheme - Sayed Abdur Rakib; Md. Sakib Hasan Khan; Khadijatul Kubra; Md. Rafiqul Islam; Md. Tanvir Hasan (AIP Advances)
This study investigates the potential optoelectronic applications of perovskite SiSnO3 by examining its structural, mechanical, electronic, and optical properties under homogeneous bulk strain. The geometrically optimized perovskite SiSnO3 has a cubic space group Pm-3m with full octahedral symmetry. The calculated negative binding energies of the proposed perovskite SiSnO3 under homogeneous bulk strain demonstrate the exothermic viability of both the intrinsic and strained structures, with the intrinsic structure being more stable. The independent elastic constants C11, C12, and C44 satisfy the Born stability criterion, confirming the mechanical stability of both intrinsic and strained structures. Our structures exhibit decreasing stiffness with increasing positive strain, but stiffness increases with negative strain. The −6%, −4%, and −2% strained structures exhibit direct bandgaps of ∼4.5 eV, making them suitable for UV detectors and sensors, whereas the 2% and 4% strained structures have indirect bandgaps, and the 6% strained structure exhibits metallic behavior. A blue shift occurs under applied strain, and reflectivity decreases with compressive strain; the −6% strained structure has the lowest reflectivity of 13% at a wavelength of ∼380 nm. Our findings suggest the potential application of perovskite SiSnO3 in advanced optoelectronic devices.